2004
DOI: 10.21236/ada428989
|View full text |Cite
|
Sign up to set email alerts
|

FASST Vegetation Models

Abstract: The one-dimensional dynamic state of the ground model FASST (Fast All-season Soil Strength) is a state of the ground model developed by Frankenstein and Koenig (2004) as part of the Army's Battlespace Terrain Reasoning and Awareness (BTRA) research program. In its original form, the only effects vegetation had on FASST were to change the surface albedo and emissivity. Recently, a two tier, multilayer vegetation algorithm was added. These can be implemented separately or together. Both alter the soil surface en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 13 publications
0
34
1
Order By: Relevance
“…Despite irregularities and amplitude variations of the temperature, the mean difference is 0.8°C, and 80% of the computed temperatures are significantly close to the experimental measurements with a relative precision of ±10% throughout the period under review, which highlights the accuracy of the model for predicting changes in the soil temperature over a long period (19 days). We also observed that, in contrast to other models [14,15,17], this model accurately predicts the temperature at night.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…Despite irregularities and amplitude variations of the temperature, the mean difference is 0.8°C, and 80% of the computed temperatures are significantly close to the experimental measurements with a relative precision of ±10% throughout the period under review, which highlights the accuracy of the model for predicting changes in the soil temperature over a long period (19 days). We also observed that, in contrast to other models [14,15,17], this model accurately predicts the temperature at night.…”
Section: Resultscontrasting
confidence: 71%
“…(14) and (27) are discretized using the implicit finite difference method, which has excellent stability and convergence. In contrast, the shortwave radiation and the latent terms are linearized at the iteration m using the same method performed in [17]:…”
Section: Numerical Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal boundary conditions were set as 21 • C for heating and 20.9 • C for cooling. The energy fluxes (Equations (1)- (6)) in Sailor's model [28] were developed from FASST vegetation model by Frankenstein and Koenig [36]. Sailor's model highlights two main fluxes: one for the soil (substrate) layer (Equation (1)) and the other for the vegetation (Equation (4)).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the computational models include heat and moisture transfer in the soil and radiant heat exchange in the canopy layer, as well as the analysis of the growth substrate in green roofs to quantify the possible reduction [1,17,19]. Among them, the most commonly used and comprehensive green roof model is the Fast All-season Soil STrength (FASST) model, established by Frankenstein and Koenig [20,21]. A large number of researchers were based upon this model to conduct analysis and simulation of green roofs [22,23].…”
Section: Introductionmentioning
confidence: 99%